2021
DOI: 10.24853/jat.6.1.15-24
|View full text |Cite
|
Sign up to set email alerts
|

Karakter Tinggi Tanaman, Umur Panen, Jumlah Anakan Dan Bobot Panen Pada 14 Genotipe Padi Lokal

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengevaluasi karakter agronomi seperti tinggi tanaman, umur panen, jumlah anakan dan bobot panen 14 genotipe padi lokal (Oryza sativa. L). Penelitian ini dilaksanakan di Desa Petapahan, Kecamatan Gunung Toar, Kabupaten Kuantan Singingi, pada bulan November 2019 hingga Maret 2020. Rancangan yang digunakan adalah Rancangan Acak Kelompok (RAK) dengan 14 perlakuan yang berasal dari genotipe padi lokal. Hasil penelitian menunjukkan pengaruh genotip yang nyata terhadap tinggi ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
7
0
4
Order By: Relevance
“…However, for the number of clumps parameter, the value is > 0.05, indicating that the observed data has no significant effect. Similar research also reported that it did not significantly affect the number of clumps [12]. Still, it did significantly increase plant height, stem diameter, number of leaves, and total leaf area.…”
Section: Number Of Clumpssupporting
confidence: 54%
“…However, for the number of clumps parameter, the value is > 0.05, indicating that the observed data has no significant effect. Similar research also reported that it did not significantly affect the number of clumps [12]. Still, it did significantly increase plant height, stem diameter, number of leaves, and total leaf area.…”
Section: Number Of Clumpssupporting
confidence: 54%
“…The rapiah variety treatment gave the highest average yield at 12 WAP, which was 20.09 cm. This height difference is due to genetic traits that have different characteristics in plant height are not only influenced by environmental factors, but also by genetic factors, when environmental conditions are the same for all genotypes, genetic factors play a more significant role in differences in plant height [7]. According to the observation results, the plant height treated with chitosan in the morning showed significantly better results than the other treatments.…”
Section: Plant Heightmentioning
confidence: 98%
“…This is because each variety differs in the number of tillers produced due to genetic factors. Moreover, each variety has genetic characteristics and traits that are one of the causes of plant appearance diversity and the result of genotypic adaptation to the environment for producing tillers [16]. A high number of productive tillers in a particular variety will produce high yields when followed by a high number of grains per panicle and a high 1000-grain weight.…”
Section: Growth and Yield Parametersmentioning
confidence: 99%